Pelatihan Mendesain Website Menggunakan Figma Pada Siswa-Siswi SMK Swasta Jambi Medan - Subhan Hafiz Nanda Ginting; Fahmi Ruziq; M. Rhifky Wayahdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Training in the field of website design using Figma has been conducted for male and female students of Private Vocational High School (SMK) Jambi Medan. The objective of this training is to provide a fundamental understanding and skills in designing layout and visual aspects of websites using the collaborative design tool, Figma. The training method involves a series of practical sessions that focus on introducing Figma, basic web design concepts, layout principles, effective use of colors and typography, as well as the implementation of interactive elements. Step-by-step guidance is given to the students in creating website designs from scratch to completion, including collaborative team processes to enhance their creativity and understanding of responsive and aesthetic design. The results of this training demonstrate an improved understanding among the students of the fundamental concepts of web design and practical proficiency in using Figma. They are capable of producing simple website designs with well-structured layouts, appropriate color choices, and suitable typography. Furthermore, the students are also capable of implementing interactive elements such as links, buttons, and dropdown menus in their designs. In conclusion, the website design training using Figma provides significant benefits for students of Private Vocational High School Jambi Medan. They have acquired foundational knowledge and practical skills in creating appealing and responsive website designs, potentially opening new opportunities in the realms of design and technology.